Robust motor drive stabilization. (August 2019) - Mosskull, Henrik
Abstract: Active stabilization of an induction motor drive fed through a poorly damped input LC filter is treated, explicitly addressing the design conflict of well damped filter quantities and small power modifications of the motors. On top of this, details of the closed-loop torque dynamics are used to assure robustness of stabilization over the entire range of operation. All this is achieved with a simple controller structure, consisting of a gain varying with the operating point and a bandpass filter. Derived results are verified through hardware-in-the-loop simulations of a traction motor drive using real control hardware.